FORMULATION AND EVALUATION OF BILAYERED FELODIPINE TRANSDERMAL PATCHES: IN VITRO AND EX VIVO CHARACTERIZATION - M, KEERTHANA; S, SHIRISHA; SUNIT KUMAR, SAHOO; RAO Y, MADHUSUDAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Felodipine (FD) is an effective Biopharmaceutics Classification System Class II calcium channel blocker mainly used in the management of hypertension and angina pectoris. It has poor solubility and low oral bioavailability (15%). To overcome these disadvantages and to maintain constant plasma concentration for maximum therapeutic activity, there is a need to design an alternative route, that is, transdermal route. The pharmacokinetic parameters make FD a suitable candidate for transdermal delivery. The present investigation consists of the study of in vitro and ex vivo skin flux of FD from bilayered transdermal patches. Methods: The patches were fabricated by solvent casting method using hydrophilic and hydrophobic polymer with different composition. Tween 80 incorporated as solubilizer, polyethylene glycol 600 as plasticizer, menthol, eucalyptus oil, and lemongrass oil used as permeation enhancers, respectively. The prepared transdermal drug delivery system was extensively evaluated for in vitro release, ex vivo permeation through pig ear skin, moisture content, moisture absorption, water vapor transmission, and mechanical properties. The physicochemical interaction between FD and polymers was investigated by Fourier-transform infrared (FTIR) spectroscopy. Results: All the formulations exhibited satisfactory physicochemical and mechanical characteristics. A flux of 35.2 μg/cm2 h, 27.9 μg/cm2 h, and 25.25 μg/cm2 h was achieved for optimized formulations containing lemongrass oil, eucalyptus oil, and menthol, respectively, permeation enhances. Values of tensile strength (0.0652±0.034 kg/mm²) and elongation at break (0.8749±0.0.0029% mm²) revealed that formulation F9 was strong but not brittle. Drug and excipients compatibility studies showed no evidence of interaction between the active ingredient and polymers. Conclusion: Bilayered FD transdermal patches could be prepared with required flux and suitable mechanical properties.